Boron‐Doped Diamond Dual‐Plate Deep‐Microtrench Device for Generator‐Collector Sulfide Sensing. Issue 11 (14th July 2015) - Harvey, Harriet M.; Gross, Andrew J.; Brooksby, Paula; Downard, Alison J.; Green, Stephen J.; Winlove, C. Peter; Benjamin, Nigel; Winyard, Paul G.; Whiteman, Matthew; Hammond, Jules L.; Estrela, Pedro; Marken, Frank
Abstract: A BDD‐BDD dual‐plate microtrench electrode with 6 μm inter‐electrode spacing is investigated using generator‐collector electrochemistry and shown to give microtrench depth‐dependent sulfide detection down to the μM levels. The effect of the microtrench depth is compared for a "shallow" 44 μm and a "deep" 180 μm microtrench and linked to the reduction of oxygen to hydrogen peroxide which interferes with sulfide redox cycling. With a deeper microtrench and a fixed collector potential at −1.4 V vs. SCE, two distinct redox cycling potential domains are observed at 0.0 V vs. SCE (2‐electron) and at 1.1 V vs. SCE (6‐electron). Abstract :